IMPACT OF LEIOMYOMA IN PREGNANCY - Navid, Sarwat; Arshad, Shahida; Ain, Qurat -ul-; Meo, Raabia Arshad (Journal of Ayub Medical College Abbottabad, 2012)
Background: Uterine fibroids or leiomyomas are benign tumours that develop in the uterus, a female reproductive organ. These cause severe complications in females during pregnancy. This study was conducted to see the impact of leiomyoma in pregnant females to make decision for its management in future. Methods: During one year of study, total 10,842 patients presented in CMH Lahore for antenatal check-up were included in the study. Out of them, 80 patients had leiomyoma in first trimester. They were followed during antenatal period. Maternal age, parity, size of fibroid, complications during pregnancy, labour and delivery, mode of delivery and indications of caesarean section were noted. Results: The prevalence of fibroids (‰¥5 Cm) in pregnant females was 0.74%. The most common complication observed was PPH (31, 38.75%) cases. Miscarriage occurred in 8 (10%) cases, cord prolepses was observed in 6 (7.5%) cases, placental abruption in 6 (7.5%) cases, placenta previa in 2 (2.5%) cases and retained placenta was observed in 1 (1.25%) case. Breech presentation was found in 10 (12.5%) cases and abdominal hysterectomy was done in 10 (12.5%) cases. Preterm labour occurred in 8 (10%) cases and IUGR was present in 5 (6.25%) cases. No maternal was reported during the study. Among all females, 64 (80%) continue their pregnancy up to term (37-40 weeks of gestation), out of which vaginal delivery occurred in 19 (29.69%) while 45 (70.3%) had LSCS due to failure in progress in 17 (37.8%), cord prolapsed in 6 (13.3%) cases, fibroid in lower segment in 3 (6.7%) cases, breech presentation in 10 (22.2%) cases and low lying placenta in 2 (4.4%) cases. Conclusion: Pregnancy with fibroid is associated with increase in caesarean section rate especially due to dysfunctional labour and malpresentation. There is also increase in incidence of postpartum haemorrhage and associated hysterectomy. Keywords: Leiomyoma, Uterine Fibroids, Benign Uterine Tumours